Impact Of The Maqasid Sharia Index Mediation On Financial And Governance Performance And Profitability Sharia Commercial Banks In Indonesia - Hadibowono, Satrio; Munandar, Agus (University of Merdeka Malang, 2023)
This study aims to explore the impact of the influence of Maqashid Syariah as a moderating variable on the variables capital adequacy ratio, operational costs, non-performance finance, Sharia supervisory board, and independent board of commissioners in influencing the profitability of Islamic banks in Indonesia. using panel data regression analysis, which is a combination of time series and cross-sectional data. The sample consists of 11 Islamic commercial banks with a time series from 2015 to 2020. The factors in the study are based on previous empirical literature. The findings show that the variables that have been moderated by Maqashid Shariah, such as the capital adequacy ratio and the Sharia supervisory board, are more significant than the variables of operational costs, non-performance finance, and the independent board of commissioners in influencing the profitability of Indonesian Sharia banking. The results of the study show that profitability growth, as measured by the moderation of the Islamic Maqashid variable on the capital adequacy ratio and the Sharia supervisory board, is a significant determinant of profitability, which implies that most of the profitability of Islamic banking in Indonesia is motivated by the capital adequacy ratio and the Sharia supervisory board, which is statistically significant. The coefficients of the capital adequacy ratio and Sharia supervisory board measures imply that these variables have a positive effect on the profitability of Islamic banking in Indonesia. The increase in profitability of Islamic banking in Indonesia, as measured by the capital adequacy ratio and the Sharia supervisory board, has a positive effect on profitability; these findings indicate that the growth of factors such as operational costs, non-performance finance, and the independent board of commissioners in influencing profitability of Indonesian Sharia banking is not motivating.